Association of PTSD Symptoms With Asthma Attacks Among Hurricane Katrina Survivors. Issue 6 (2nd December 2014) - Arcaya, Mariana C.; Lowe, Sarah R.; Rhodes, Jean E.; Waters, Mary C.; Subramanian, S. V.
Abstract : The relationship between posttraumatic stress disorder (PTSD) and asthma in the wake of natural disasters is poorly understood. Using pre‐ and postdisaster data ( N = 405) from the Resilience in Survivors of Katrina (RISK) project, we examined associations between PTSD symptoms, measured by the Impact of Event Scale‐Revised (IES‐R), and self‐reported postdisaster asthma attacks. A 1‐point increase in the IES‐R avoidance score, which corresponded to one standard deviation change in this sample, was associated with double the odds of reporting an asthma attack or episode since the hurricane, 95% CI Revise spacing among characters: [1.22, 4.16]. Association with hyperarousal and intrusion symptoms was null. Further research using objective measures of asthma morbidity is needed; nevertheless, these findings may help inform postdisaster health services delivery and predisaster mitigation planning.